Lung tensioning device coil treatment in patients with severe emphysema: a prospective safety and feasibility trial (EFFORT) - Roodenburg, Sharyn; Klooster, Karin; Hartman, Jorine E.; Kontogianni, Konstantina; Brock, Judith; Dittrich, A. Susanne; van Dijk, Marlies; Koster, T. David; Herth, Felix; Slebos, Dirk-Jan (Respiration, 2025)
Introduction: Currently, there is a lack of bronchoscopic lung volume reduction options that do not depend on fissure integrity. Endobronchial coils have been extensively studied to address this need but exhibited variable patient response and have been discontinued. Lung tension device (LTD) coils represent the next-generation coil treatment. This study aimed to evaluate safety, feasibility, and efficacy of LTD-coil treatment. Methods: Patients with advanced emphysema and hyperinflation were enrolled at two European sites. LTD-coils (Free Flow Medical, Fremont, CA, USA) were implanted in the two most destructed lobes, as determined by quantitative CT analysis, in two separate procedures. The primary endpoint was 3-month follow-up after the last treatment. Results: Fourteen patients (50% male, median age 64 years, FEV1 23%predicted, RV 249%predicted) received LTD-coil treatment: 12 received bilateral and 2 unilateral treatment. Six serious respiratory adverse events occurred within the initial 3 months posttreatment, including one device-associated death. Treatment significantly reduced in- and expiratory volume of the treated lobes (−410 [−710, −340], p = 0.004 and −650 [−730, −190] mL, p < 0.001, respectively) and improved quality of life (SGRQ total score −4.6 [−21.0, −2.6], p < 0.001). However, at a group level, no significant improvements in pulmonary function or 6-min walk distance were observed. Responder rates ranged from 18% to 54% for the different endpoints. Conclusion: This first-in-human study shows that the new LTD-coil procedure is feasible with a safety profile comparable to the previous coil treatment. While the treatment effectively reduced lobar volume and modestly improved quality of life up to 3 months’ follow-up, at a group level it did not significantly enhance pulmonary function or exercise capacity.
Online veröffentlicht: September 16 2024
Gesehen am 02.04.2025